Renal Tumors in Adults: The Clinical Experience of 124 Patients - Abdulmalik M. Tayib, (Journal of King Abdulaziz University: Medical Sciences, 2023)
To evaluate the clinical presentation and surgical management of adult patients who were presented with renal cancer, and to compare it with findings in the international studies as to give recommendations regarding future management in Saudi Arabia. 124 adult patients were included in the study. The data were reviewed for all patients. All data were entered and analyzed; the statistics obtained were the minimum values, maximum values, mean value and standard deviations. The age of the patients varied between 27 86 years old with a mean age of 54.08 (±10.75) years, 96 (77.42%) patients were males while 28 (22.58%) were females. For clinical presentation, 32 (25.8%) patients were asymptomatic diagnosed during a general check up, 44 (35.5%) patients presented with gross hematuria, 14 (11.29%) patients presented with palpable masses, and 42 (33.87%) patients presented with flank pain. Among all renal tumor histological subtypes, conventional clear cell cancer was found in 66 (53.22%) patients, while transitional cell cancer was documented in 8 (6.45%) patients. Renal cancer is not a common disease. This study demonstrated the presence of some different clinical and pathological presentation than what has been reported in the literature. Multicenter national studies are needed to improve the outcomes for the management of renal cancer.